Attention triggers and investors’ risk-taking - Arnold, Marc; Pelster, Matthias; Subrahmanyam, Marti G. (Journal of Financial Economics, 2022)
This paper investigates how individual attention triggers influence financial risk-taking based on a large sample of trading records from a brokerage service that sends standardized push messages on stocks to retail investors. By exploiting the data in a difference-in-differences (DID) setting, we find attention triggers increase investors’ risk-taking. Our DID coefficient implies attention trades carry, on average, a 19 percentage-point-higher leverage than non-attention trades. We provide a battery of cross-sectional analyses to identify the groups of investors and stocks for which this effect is stronger.